Pemurnian Bioetanol dengan Distilasi Rektifikasi Tipe ‘Sieve Tray’ untuk Menghasilkan FGE (Fuel Grade Etanol) - Yuana Susmiati; Mochamad Nuruddin; Agus Nursalim (Politeknik Negeri Jember, 2017)
Bioethanol can be used as a substitution of fosil fuel as a fuel stove or motor vehicle. In the ordinary distillation bioethanol production process is only able to produce 50-70% of ethanol which can only be used to fuel stove. To obtain high-grade bioethanol, a multilevel distillation process is required. One of the distillation methods to purify bioethanol is rectification distillation. The purpose of this research is to design a sieve tray type rectifier distillation apparatus that used to increase the bioethanol content. The results showed that the device can increase the ethanol content from 37% to 90%.